2008
DOI: 10.1002/andp.200710287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light waves on the thermoelectric power under large magnetic field in III-V, ternary and quaternary materials

Abstract: Key words Light waves, thermoelectric power, III-V, ternary and quaternary materials. PACS 73.50.Pz, 78.55.Cr We study theoretically the influence of light waves on the thermoelectric power under large magnetic field (TPM) for III-V, ternary and quaternary materials, whose unperturbed energy-band structures, are defined by the three-band model of Kane. The solution of the Boltzmann transport equation on the basis of this newly formulated electron dispersion law will introduce new physical ideas and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…= Tr ρs (t) ĵth,i (r) (11) calculated by the expectation value of the spin polarization current density operator [24].…”
Section: Transport Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…= Tr ρs (t) ĵth,i (r) (11) calculated by the expectation value of the spin polarization current density operator [24].…”
Section: Transport Formalismmentioning
confidence: 99%
“…On the other hand, the influences of light on thermoelectric effects have been investigated and shown that the thermoelectric power can be enhanced by increasing the intensity of light [11]. It was also found that a polarized light can induce a Fano-like resonance in the thermal conductance [12].…”
Section: Introductionmentioning
confidence: 99%
“…The electron concentration can be written as 13 is the broadening parameter in this case, and M 23 D 1 C A 2 13 C 2A 13 cos H 13 .…”
Section: Magnetothermopower In Quantum Dots Of N-germaniummentioning
confidence: 99%
“…13 Plot of the normalized TPSM in QDs of InSb as a function of carrier concentration for all the cases ofFig. 1.9…”
mentioning
confidence: 99%